BACTERIAL ð›‚-AMYLASE ACTIVITY ON THE STARCH PRESENT IN MAIZE KERNEL. - Vyas, Priya; Shirsat, Mrunal (Innoriginal: International Journal of Sciences, 2017)
The purpose of the present research work was to investigate the feasibility of production of alpha amylase enzyme from three bacterial species Bacillus subtilis, Bacillus licheniformis and Lactobacillus acidophilusand to check their applicability on maize starch hydrolysis. These bacteria are able to produce alpha amylase enzyme in nutrient medium. This amylase is generally responsible for starch hydrolysis, through this study Â we can find the alternative mean for the starch digestion.As with the age alpha amylase production becomes reduced in human body. The enzyme alpha amylase is required to digest the starch. So, scarcity of this enzyme in body may cause many diseases associated with carbohydrate, like diabetes and colon cancer. So, when the metabolic rate becomes down and alpha amylase production is not properly achieved then to digest the food starch in our bodywe can give this extracted alpha amylase from bacteria in some form. The present study was focused on the alpha amylase production from three bacterial species and comparative study of them to hydrolyse the maize starch. Key words:Bacillus subtilis, Bacillus licheniformis, Lactobacillus acidophilus, and the alpha amylase.